P693 Should extraintestinal manifestations (EIMs) be part of disease activity assessment in ulcerative colitis?. (16th January 2018) - Walsh, A; Kormilitzin, A; Hinds, C; Sexton, V; Wilson, J; Brain, O; Keshav, S; Uhlig, H; Geddes, J; Goodwin, G; Peters, M; Collins, G; et al.
Abstract: Background: The Simple Clinical Colitis Index (SCCAI) is a clinical index specific to ulcerative colitis (UC). The SCCAI is comprised of six descriptors: daytime bowel frequency, nocturnal bowel frequency, urgency, bleeding, general well-being and EIMs. Four out of a total of 19 points are allocated to EIMs: arthritis, uveitis, erythema nodosum (EN), pyoderma gangrenosum (PG). It is increasingly clear that the major determinant of EIMs are genetic rather than due to underlying disease activity. Physicians question whether the presence or absence of EIMs have any place in an index designed to capture disease activity. Methods: TrueColours UC is a comprehensive real-time web-based programme for patients with UC. It monitors multiple parameters via electronic questionnaires. A prospective, non-randomised 6-month pilot study recruited patients from the Oxford Inflammatory Bowel Disease service. The pilot collected daily SCCAI responses from 66 patients over a 6 month period. These SCCAI data were interrogated, with the specific aim of evaluating the merit of including EIMs in the SCCAI. Five approaches were taken: (1) frequency of reporting and frequency analysis for EIMs, (2) correlation between EIMs and other descriptors of the SCCAI, (3) factor analysis (measure of variability among descriptors), (4) item-total correlation (whether EIMs correlate well with overall SCCAI), and (5) Cronbach's alpha (a measure of internal consistency). Results: A total of 8741 (median 151, IQR 102–180) SCCAI measurements were submitted during the 6-month period. The number of patients reporting arthritis, uveitis, EN and PG were 31, 9, 5, and 1, respectively. Frequency analysis revealed that 76% of all SCCAI responses reported zero for EIMs. Repeated measurement correlation showed that EIMs correlated poorly with all other SCCAI descriptors: bowel frequency 0.07 (95% CI 0.05–0.07), nocturnal frequency 0.04 (95% CI 0.02–0.06), urgency 0.12 (95% CI 0.10–0.15), blood in stool 0.07 (95% CI 0.05–0.09), general well-being 0.15 (95% CI 0.13–0.17). Factor analysis identified that one of the latent factors was EIMs alone. The item-total correlation for EIMs was 0.14 (95% CI 0.12–0.16). Cronbach's alpha for the total SCCAI was 0.66 (95% CI 0.65–0.67), with removal of EIMs improving this to 0.68 (95% CI 0.67–0.74). Conclusions: Data from this pilot indicate that EIMs should be removed from the SCCAI. EIMs need to be independently assessed, but not as part of UC disease activity assessment.